1999
DOI: 10.1016/s1097-2765(00)80216-6
|View full text |Cite
|
Sign up to set email alerts
|

Activation Domain–Mediated Targeting of the SWI/SNF Complex to Promoters Stimulates Transcription from Nucleosome Arrays

Abstract: The yeast SWI/SNF complex is required for the transcription of several yeast genes and has been shown to alter nucleosome structure in an ATP-dependent reaction. In this study, we show that the complex stimulated in vitro transcription from nucleosome templates in an activation domain-dependent manner. Transcription stimulation by SWI/SNF required an activation domain with which it directly interacts. The acidic activation domains of VP16, Gcn4, Swi5, and Hap4 interacted directly with the purified SWI/SNF comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
215
0
4

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(233 citation statements)
references
References 52 publications
14
215
0
4
Order By: Relevance
“…Results presented here indicate that the high levels of histone acetylation mediated by VP16, and its ability to recruit ATP-dependent chromatin remodeling complexes and histone acetyltransferases (65)(66)(67), are sufficient to fully abrogate the spreading of SIR complexes. In this assay, VP16 acts to increase histone acetylation on both sides of its binding site, thereby activating nearby genes irrespective of their location relative to the telomere, as expected from a local increase of HAT concentration.…”
Section: Discussionmentioning
confidence: 79%
“…Results presented here indicate that the high levels of histone acetylation mediated by VP16, and its ability to recruit ATP-dependent chromatin remodeling complexes and histone acetyltransferases (65)(66)(67), are sufficient to fully abrogate the spreading of SIR complexes. In this assay, VP16 acts to increase histone acetylation on both sides of its binding site, thereby activating nearby genes irrespective of their location relative to the telomere, as expected from a local increase of HAT concentration.…”
Section: Discussionmentioning
confidence: 79%
“…This could occur through recruitment of chromatin-modifying complexes such as the SWI-SNF complex, or complexes capable of modifying histones, such as the GCN5-containing SAGA complex (14,26,45,55,56,65,72,83). The strong and general capability of artificially recruited GAL11 to activate transcription and to remodel the PHO5 promoter (18,21,22) suggests that such chromatin-modifying activity can be recruited along with the holoenzyme (76).…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that activators recruit any of various candidate chromatin remodeling complexes, which in turn alter local chromatin structure. This local remodeling could occur via histone acetylation following recruitment of GCN5 in the SAGA complex (72) or by alteration of histone-DNA interactions by the SWI-SNF complex, among other possibilities (14,45,55,56,65,83). In promoters that have a nucleosome positioned in close proximity to or incorporating the TATA element, such chromatin remodeling might be required to make the TATA element accessible to TFIID.…”
mentioning
confidence: 99%
“…Recent work indicates that genespeci®c activators target remodelling complexes to regulatory regions by directly interacting with them (Neely et al, 1999;Yudkovsky et al, 1999). These interactions are mediated by the activation domains of the transcription factors, which have been shown to recruit SNF/SWI remodelling activity to nucleosomal templates in vitro (Neely et al, 1999;Yudkovsky et al, 1999).…”
Section: Transactivator-dependent Nucleosome Remodelling Complexes Anmentioning
confidence: 99%
“…Recent work indicates that genespeci®c activators target remodelling complexes to regulatory regions by directly interacting with them (Neely et al, 1999;Yudkovsky et al, 1999). These interactions are mediated by the activation domains of the transcription factors, which have been shown to recruit SNF/SWI remodelling activity to nucleosomal templates in vitro (Neely et al, 1999;Yudkovsky et al, 1999). Several authors have also reported the activatormediated targeting of chromatin remodelling complexes to transcriptional regulatory regions in vivo (Cosma et al, 1999;Fryer and Archer, 1998;KowenzLeutz and Leutz, 1999;Lee et al, 1999a).…”
Section: Transactivator-dependent Nucleosome Remodelling Complexes Anmentioning
confidence: 99%